Challenges in software applications for the cognitive evaluation and stimulation of the elderly - Rute-Pérez, Sandra; Hurtado, María Visitación; Rodríguez-Fórtiz, María José; Caracuel, Alfonso; Santiago-Ramajo, Sandra (Journal of NeuroEngineering and Rehabilitation, 2017)
Background Computer-based cognitive stimulation applications can help the elderly maintain and improve their cognitive skills. In this research paper, our objectives are to verify the usability of PESCO (an open-software application for cognitive evaluation and stimulation) and to determine the concurrent validity of cognitive assessment tests and the effectiveness of PESCO’s cognitive stimulation exercises. Methods Two studies were conducted in various community computer centers in the province of Granada. The first study tested tool usability by observing 43 elderly people and considering their responses to a questionnaire. In the second study, 36 elderly people completed pen-and-paper and PESCO tests followed by nine cognitive stimulation sessions. Meanwhile, a control group with 34 participants used computers for nine non-structured sessions. Results Analysis of the first study revealed that although PESCO had been developed by taking usability guidelines into account, there was room for improvement. Results from the second study indicated moderate concurrent validity between PESCO and standardized tests (Pearson’s r from .501 to .702) and highlighted the effectiveness of training exercises for improving attention (F = -4.111, p < .001) and planning (F = 5.791, p < .001) functions. Conclusions PESCO can be used by the elderly. The PESCO cognitive test module demonstrated its concurrent validity with traditional cognitive evaluation tests. The stimulation module is effective for improving attention and planning skills.
Keywords: application software; software design; cognitive evaluation; cognitive stimulation; aging; JCR; Scopus